BS EN ISO 10893-2 AMD1. Non-destructive testing of steel tubes. Part 2. Automated eddy current testing of seamless and welded (except submerged arc-welded) steel tubes for the detection of imperfections (27th August 2019) - British Standards Institution,
No abstract available